A consistency mapping for the effects on enzymatic hydrolysis sugar yield using two sugar yield definitions in cellulosic biofuel manufacturing - Zhang, Meng; Song, Xiaoxu; Deines, Timothy W.; Pei, Zhijian J.; Wang, Donghai (My University, 2014)
Two different sugar yield definitions (cellulose-based and biomass-based) were used in reported studies investigating the relationship between biomass particle size and enzymatic hydrolysis sugar yield. It is noticed that these reported relationships are not consistent if sugar yield is defined differently. The literature does not contain any reports on the effects of sugar yield definition on the relationship between biomass particle size and enzymatic hydrolysis sugar yield. This paper presents a consistency mapping to show under what conditions the relationships are consistent (or inconsistent) when these two definitions are used. The application of this mapping is illustrated via an experimental study with poplar wood biomass on the relationship between biomass particle size and enzymatic hydrolysis sugar yield using both sugar yield definitions. The application of this mapping is also illustrated via data reported in the literature. Not limited to particle size, this mapping is applicable to investigations of the relationships between a variety of parameters (biomass type, pretreatment condition, etc.) and enzymatic hydrolysis sugar yield.
Keywords: Biofuel; Cellulosic biomass; Enzymatic hydrolysis; Particle size; Sugar yield